Panzhousaurus rotundirostris Jiang et al., 2019 (Diapsida: Sauropterygia) and the recovery of the monophyly of Pachypleurosauridae. Issue 1 (2nd January 2021) - Lin, Wen-Bin; Jiang, Da-Yong; Rieppel, Olivier; Motani, Ryosuke; Tintori, Andrea; Sun, Zuo-Yu; Zhou, Min
ABSTRACT: Panzhousaurus rotundirostris Jiang, Lin, Rieppel, Motani and Sun, 2019, is restudied on the basis of a second specimen from the Upper Member of the Guanling Formation near Panzhou City, Guizhou Province, China. The second specimen offers hitherto unknown or unconfirmed information regarding the dermal palate, the ventral aspect of the cervical vertebrae, and the hind limbs, thus permitting a refinement of the diagnosis. Newly added or modified diagnostic characters include paired frontals with no posterolateral process, elongated and slender phalanges in the manus and pes, and a phalangeal formula of 3-4-5-4-3 for the manus, and 2-3-4-5-3 for the pes. A new phylogenetic analysis of Eosauropterygia demonstrates that Pachypleurosauridae is the sister taxon of Eusauropterygia, and the monophyly of these groups as traditionally upheld is confirmed. Panzhousaurus is most closely related to Dianopachysaurus and Keichousaurus within Pachypleurosauridae. In this study, the monophyletic Pistosauroidea excludes Corosaurus and Cymatosaurus . The latter two genera are found to form a monophyletic clade that represents the basal-most members of Eusauropterygia, which is in accordance with their stratigraphic distribution.